Panel 1: Role of the Architect (EAAE Annual Conference Proceedings, 2023)
Panel moderated by Osamu Okamura, Architect, teacher and Dean of the Faculty of Arts and Architecture of the Technical University in Liberec / FUA TUL. The panel was opened with a lecture by Jenny B. Osuldsen (Snøhetta). "Whatever the stage of a project – from ideation to finalisation – an architect’s most important job is to communicate the ideas of the architectural project. By developing narratives and diagrams, these ideas can be communicated and brought to life. What is most important is being open to the process of dialogue between site, context, humans, and history and to the unknown of the future – conveying complicated structures and creations through emotion, aesthetics and experiences. This role in communication helps architecture to be seen through project narratives, processes and experiences created along the way to designing newly built projects visualised through a selection of Snøhettas projects. Snøhetta is interdisciplinary."